Mengembangkan Motorik Halus Anak Berkebutuhan Khusus Melalui Kegiatan Meronce Di Paud Inklusi Family Club Cianjur - Qudsi Mutawakil Husaini; Arif Ahmad Fauzi; Dini Fauziah Agustini; Nanda Rembulan (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Children with special needs are children with characteristics that are not the same as other normal children because they experience physical, mental, social and emotional limitations that affect their growth and development process. One of the disorders that occur in children with special needs is the difficulty in developing their fine motor skills. Children with special needs who have insufficient fine motor skills will be given media related to fine motor development, one of which is by carrying out meronce playing activities. The purposes of this study were 1) To find out how meronce play therapy develops fine motor skills in Children with Special Needs in PAUD Inclusion Family Club Cianjur, 2) To find out the factors that influence the development of meronce activities in Children with Special Needs in PAUD Inclusion Family Club Cianjur. This study used a descriptive qualitative approach using a purposive sampling technique. While data collection techniques using observation techniques, interviews and documentation. The data analysis technique uses three things, namely data collection, data reduction, and data presentation. While the conclusions and validity of the data using triangulation of sources and techniques. This study came to the conclusion that playing meronce can develop fine motor skills in children with special needs. The results showed that fine motor skills in children with special needs developed after being given meronce play therapy. 2) Factors that influence the development of fine motor skills come from a harmonious relationship between teacher and student, parenting style, and stimulus.